AI-driven content strategies: enhancing consumer engagement and loyalty - Bilro, R.G. (2025 Global Marketing Conference at Hong-Kong, 2025)
This study investigates the impact of Self-Brand Connection, AI-Driven Personalization, Content Relevance, and Content Effectiveness on Online Brand Customer Engagement (OBCE), and how OBCE influences Purchase Intention and Brand Advocacy. Using quantitative methods and a questionnaire survey, data is collected from online consumers. The findings intends to validate the proposed conceptual model, highlighting the critical role of AI-enhanced content in shaping consumer behaviors and enhancing marketing strategies. The study underscores the transformative potential of AI in digital marketing.